Variety of Bryophytes in Sultan Adam Mandiangin Grand Forest Park Area - Khairun Amalia; Aulia , Ajizah; Nurul Hidayati, Utami (BIOVALENTIA: Biological Research Journal, 2024)
Moss plants can live well in areas that have high humidity. The Dutch Guesthouse which is located in the Sultan Adam Mandiangin Forest Park area has high humidity because the area has lots of dense plants, so it is a suitable habitat for the living nature of moss plants. This study aims to describe and identify the various species of moss found in the area of study. Data collection was carried out using the exploring method, followed by determining and identifying each sample of the moss plants found in the laboratory. Data analysis was carried out descriptively and identifying species with reference to the relevant literatures. The results found 10 species of mosses belonging to 7 different families, both found in tree, rock and soil habitats. The species found were: Calymperes tenerum, Calymperes afzelii, Hyophila apiculata, Hyophila involuta, Ectropothecium falciforme, Octoblepharum albidum, Philonotis hastata, Acroporium secundum, Lejeunea lamacerina, and Thysananthus sp. The results of this study are expected to provide information about the variety and biodiversity of mosses in South Kalimantan.